Music, Architecture, Proportion and the Renaissance Way of Thinking. (13th April 2021) - Zara, Vasco
Abstract : During the Renaissance, the language of proportion became a unified theory capable of encompassing the understanding of the world within a coherent theological, philosophical and artistic framework. Music, with its harmonic paradigm, plays a key role in this construction. From the fifteenth century through to the end of the sixteenth century, architects and architectural theorists made reference, both in new treatises and commentaries to Vitruvius, to musical matters, transforming architecture into the summa of knowledge. The affinity to music was grounded on both a common mathematical and rhetoric gnosiology. Formerly conceived of as ideal, numbers became eloquent, reinforcing the quantitative paradigm of proportion with its qualitative one. The language of proportion as a compositional tool reveals the shift between the Middle Ages and the Renaissance: while the Medieval tèchne based on modular thinking provides beauty and universal truth using the technique of repetition, the Humanist paradigm of variety produces pleasure and individual truth – a condition typical of the premodern.